Chelate Silylene–Silyl Ligand Can Boost Rhodium‐Catalyzed C−H Bond Functionalization Reactions - Mo, Zhenbo; Kostenko, Arseni; Zhou, Yu‐Peng; Yao, Shenglai; Driess, Matthias (Chemistry : a European journal, 2018)
The first N‐heterocyclic silylene (NHSi)–silane scaffold LSi−R−Si(H)Mes2 (1) (L=PhC(NtBu)2; R=1,12‐xanthendiyl spacer; Mes=2,4,6‐Me3C6H2) was synthesized and used to form the unique rhodium(III) complex (LSi−R−SiMes2)Rh(H)Cl 2 through its reaction with 0.5 molar equivalents of [Rh(coe)2Cl]2 (coe=cyclooctene). An X‐ray diffraction analysis revealed that 2 has a (SiIISiIV)Rh(H)Cl core with three short Rh⋅⋅⋅H−C contacts with Me groups of the ligand 1, which cause a distorted pentagonal bipyramidal coordination of the Rh center. Unexpectedly, the reaction of 2 with tBuONa gives the new bis(silyl)hydridorhodium(III) complex 4. Due to the strong donor ability of the chelate SiII–SiIV ligand, 2 and 4 can act as highly efficient pre‐catalysts in the Rh‐mediated selective C−H functionalization of 2‐phenylpyridines with C−C unsaturated organic substrates under mild reaction conditions. Agostic complexes: A pentagonal‐bipyramidal rhodium(III) complex featuring one agostic and two anagostic interactions with a new SiII–SiIV ligand has been synthesized. It can be used as pre‐catalyst for alkenylation and alkylation of C−H bonds with high catalytic efficiency under mild reaction conditions (see scheme).